Assessment of DPY19L2 Deletion in Familial and Non-Familial Individuals with Globozoospermia and DPY19L2 Genotyping - Parastoo Modarres; Somayeh Tanhaei; Marziyeh Tavalaee; Kamran Ghaedi; Mohammad Reza Deemeh (International Journal of Fertility and Sterility, 2016)
Background Globozoospermia is a rare syndrome with an incidence of less than 0.1% among infertile men. Researchers have recently identified a large deletion, about 200 kbp, encompassing the whole length of DPY19L2 or mutations in SPATA16 and PICK1 genes associated with globozoospermia. The aim of this study was to analyze the DPY19L2 gene deletion using polymerase chain reaction technique for the exons 1, 48, 11 and 22 as well as break point (BP) “a” in globozoospermic men. Materials and Methods In this experimental study, genome samples were collected from 27 men with globozoospermia (cases) and 36 fertile individuals (controls), and genomic analysis was carried out on each sample. Results Deletion of DPY19L2 gene accounted for 74% of individuals with globozoospermia. DPY19L2 gene deletion was considered as the molecular pathogenic factor for the onset of globozoospermia in infertile men. By quantitative real-time polymerase chain reaction (qPCR), we genotyped DPY19L2 deletion and identified carriers within the population. Conclusion This technique may be considered as a method for family counseling and has the potential to be used as a pre-implantation genetic diagnosis, especially in ethnic community with high rate of consanguineous marriages.